The Implementation of SIAKBA in Recruiting Ad Hoc Bodies for the Medan City General Election Commission: An Islamic Meritocracy Perspective on the Challenges of Electoral Democracy - Nyak Maysa; Junaidi; Mardian Idris Harahap; Agung Prayogo Prayogo (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2026)
The recruitment of ad hoc election management bodies constitutes a critical stage in ensuring the quality and integrity of democratic elections. Although the General Election Commission (KPU) has implemented the KPU and Ad Hoc Membership Information System (SIAKBA) as a digital platform to enhance efficiency, objectivity, and accountability in the recruitment process, its implementation continues to face challenges, particularly the low level of public trust in the transparency of selection outcomes and the perception that personal connections may influence recruitment decisions. This study aims to analyze the implementation of SIAKBA in the recruitment of ad hoc election officials for the 2024 Medan City Election from the perspective of Islamic meritocracy while identifying mitigation strategies to strengthen recruitment governance. This study employed a qualitative approach using observation, in-depth interviews, and document analysis involving election management officials in Medan City. The findings reveal that the implementation of SIAKBA has complied with the procedural requirements stipulated by Indonesian electoral laws and KPU regulations, reflecting the principles of Islamic meritocracy through the application of al-kafā'ah, al-amānah, al-'adālah, iḥtiyāṭ, al-raqābah, al-musāwah and collaborative governance. Nevertheless, the system has not yet fully succeeded in fostering public trust due to the limited transparency of participants' assessment results. This study highlights the need to strengthen transparency mechanisms by providing measurable, objective, and publicly accessible final selection results in order to enhance the legitimacy of the recruitment process and reinforce public confidence in future electoral administration.